Prevalence, sociodemographic and clinical characteristics of G6PD deficient blood donors in Terengganu and the effects of storage on their donated blood - Mansor, Hayati; Mohd Tohit, Eusni Rahayu; Idris, Faridah; Awang Abd Rahman, Alawiyah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Glucose-6-phosphate dehydrogenase (G6PD) deficiency causes red blood cell destruction due to oxidative stress. G6PD is essential for NADPH conversion; which is critical for glutathione reductase to prevent damage to cellular structures. In Malaysia, blood donors are not routinely screened for G6PD deficiency. We hypothesise that G6PD-deficient red blood cells are more likely to haemolyse during storage due to increased oxidative molecules. The objectives of this study were to determine the prevalence of G6PD deficiency among blood donors, describe their characteristics and to evaluate the effects of storage on G6PD-deficient donated blood. Methods: This study was conducted at selected mobile donation centres in Terengganu. Consented blood donors were screened for G6PD status using fluorescent spot tests (FST). G6PD enzyme activities were measured for donors who were G6PD deficient. Effects of storage on haemolysis from G6PD-deficient donors were compared with non G6PD-deficient group. Sixty ml of blood was collected from blood unit to transfer pouch for estimation of haemoglobin (Hb), plasma Hb, percentage of haemolysis and plasma potassium. Serial sampling with a 7-day interval was done from Day 1 to Day 35. Statistical analysis was considered significant if p ≤0.05. Results: A total of 440 blood donors were screened and 12 male donors were found to be G6PD deficient by FST. Enzymatic activities were measured in 11 donors as one donor sample failed to be sent to the centre due to logistic problem. Their enzymatic activities ranged from 1.66-2.93 U/g Hb whereby 6 have severe deficiency and the other 5 were categorised as partial deficiency. Donors were asymptomatic for haemolytic episode. Serial sampling showed there was no significant difference of haemolytic parameters in blood units of G6PD-deficient donors as compared to control (p>0.05). Conclusion: Prevalence of G6PD blood donors in Terengganu mobile centres was 2.7%. G6PD enzyme activities did not correlate with clinical symptoms. Haemolytic parameters were not affected in blood units which were G6PD-deficient.